Health-risk assessment related to the fluoride, nitrate, and nitrite in the drinking water in the Sanandaj, Kurdistan County, Iran. Issue 5 (4th July 2019) - Rezaei, Hadi; Jafari, Ali; Kamarehie, Bahram; Fakhri, Yadolah; Ghaderpoury, Afshin; Karami, Mohammad Amin; Ghaderpoori, Mansour; Shams, Mahmuod; Bidarpoor, Farzam; Salimi, Mohammad
ABSTRACT: The concentration of fluoride and nitrate in groundwater is usually higher than that of surface water. The main objective of this study was to estimate the health-risk assessment associated with fluoride, nitrate, and nitrite in drinking water in Sanandaj and its villages. The number of samples in the Sanandaj and its rural was 106. The average concentration of fluoride in urban and rural drinking water was 0.22 mg/l and 0.27 mg/l, respectively. Fluoride concentration was also close to urban and rural drinking water. The concentration of nitrate in urban and rural drinking water was in the range between 0.28–27.77 mg/l and 1.28–80 mg/l, respectively. The concentration of nitrate reported in rural samples was higher than that of urban samples. The maximum concentration of nitrate reported in this study was 80 mg/l. The mean CDI for nitrate in the men, women, and children was 0.4258, 0.5110, and 1.1454, respectively. The findings of this study indicated that all three groups studied were exposed to nitrate contact hazards (HQ > 1). Therefore, the HQ in each of the three groups was higher than 1, which should be carefully monitored and necessary measures should be performed.